MENGHIDUPKAN SUASANA LEWAT SUARA: MEDIA INTERAKTIF MUSIK ILUSTRASI DALAM PEMBELAJARAN SENI MUSIK SMA - Alexander Satria Teguh Prasetya; Dwi Kusumawardani; Dian Herdiati (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This study aims to develop and test the effectiveness of interactive teaching media based on illustrated music in music art learning in Senior High Schools (SMA). The background of this study is the lack of active participation of students in conventional learning about illustrated music, which functions to strengthen the emotional atmosphere in the narrative. By utilizing digital technology, a multimedia application-based teaching media was developed to encourage students' exploration and creativity. This study uses the Borg and Gall Research and Development (R&D) model method, with subjects of grade XI students at one of the state high schools in Jakarta. Data collection was carried out through observation, interviews, questionnaires, and pre-tests and post-tests, which were then analyzed qualitatively and quantitatively. The results of the study showed that this interactive teaching media was effective in increasing conceptual understanding, improving the learning atmosphere, and encouraging students' creativity. This is evidenced by the average increase in post-test scores of 24% and positive responses from students who stated that this media was interesting and easy to use. This media successfully supports project-based and constructivist learning, where students actively create meaning. These findings contribute to the development of music art learning strategies in the digital era, showing the great potential of interactive media for strengthening cultural literacy and character building of students. ABSTRAK Penelitian ini bertujuan untuk mengembangkan dan menguji keefektifan media ajar interaktif berbasis musik ilustrasi dalam pembelajaran seni musik di Sekolah Menengah Atas (SMA). Latar belakang penelitian ini adalah kurangnya partisipasi aktif siswa dalam pembelajaran konvensional mengenai musik ilustrasi, yang berfungsi memperkuat suasana emosional dalam narasi. Dengan memanfaatkan teknologi digital, sebuah media ajar berbasis aplikasi multimedia dikembangkan untuk mendorong eksplorasi dan kreativitas siswa. Penelitian ini menggunakan metode Research and Development (R&D) model Borg dan Gall, dengan subjek siswa kelas XI di salah satu SMA negeri di Jakarta. Pengumpulan data dilakukan melalui observasi, wawancara, angket, serta pre-test dan post-test, yang kemudian dianalisis secara kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa media ajar interaktif ini efektif meningkatkan pemahaman konsep, memperbaiki suasana belajar, dan mendorong kreativitas siswa. Terbukti dari rata-rata peningkatan nilai post-test sebesar 24% dan respons positif siswa yang menyatakan media ini menarik serta mudah digunakan. Media ini berhasil mendukung pembelajaran berbasis proyek dan konstruktivistik, di mana siswa aktif menciptakan makna. Temuan ini berkontribusi pada pengembangan strategi pembelajaran seni musik di era digital, menunjukkan potensi besar media interaktif untuk penguatan literasi budaya dan pembentukan karakter siswa.